2018
DOI: 10.1021/acs.langmuir.8b02465
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Hydrogel Capsules of Interpenetrated Network for Encapsulation of Small Molecules

Abstract: We report on a facile capsule-based platform for efficient encapsulation of a broad spectrum of hydrophilic compounds with molecular weight less than 1000 g mol. The encapsulated compounds extend from low-molecular-weight anionic Alexa Fluor 532 dye and cationic anticancer drug doxorubicin (DOX) to fluorescein isothiocyanate-dextrans with M ranging from 4000 to 40 000 g mol. The pH-sensitive hydrogel capsules with an interpenetrated network shell are synthesized by layer-by-layer assembly of poly(methacrylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…As reported previously, the cystamine-crosslinked PMAA network demonstrated pH-dependent swelling at pH > 6 and pH < 5 because of ionization of carboxylic and amine groups, respectively, similar to that observed for PMAA multilayer hydrogels cross-linked with ethylenediamine [34,63]. However, we have shown earlier that the entrapment of PVPON within the capsule wall as well as a high crosslink density can drastically change the pH-swelling profile of (PMAA/PVPON) hydrogels [71]. Thus, the presence of long PVPON chains highly entangled within the PMAA capsule hydrogel shell was shown to suppress mobility of PMAA segments between the crosslinks.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…As reported previously, the cystamine-crosslinked PMAA network demonstrated pH-dependent swelling at pH > 6 and pH < 5 because of ionization of carboxylic and amine groups, respectively, similar to that observed for PMAA multilayer hydrogels cross-linked with ethylenediamine [34,63]. However, we have shown earlier that the entrapment of PVPON within the capsule wall as well as a high crosslink density can drastically change the pH-swelling profile of (PMAA/PVPON) hydrogels [71]. Thus, the presence of long PVPON chains highly entangled within the PMAA capsule hydrogel shell was shown to suppress mobility of PMAA segments between the crosslinks.…”
Section: Resultsmentioning
confidence: 54%
“…Specifically, when the molecular weight of PVPON in PMAA/PVPON hydrogen-bonded multilayer template films was increased to 1,300,000 Da (1300 kDa), only 18% of the PVPON content was released due to the increased chain entanglement in comparison to shorter (58 kDa) PVPON polymer chains [76]. In another recent study, we have demonstrated that hydrogel capsules made of interpenetrated (PMAA/PVPON) multilayers can be obtained by dipped multilayer assembly of PMAA ( M w = 150,000 Da) and PVPON ( M w = 1,300,000 Da) on porous and solid silica microparticles followed by chemical crosslinking of PMAA [71]. Because of its high molecular weight, PVPON was physically entrapped within the PMAA network and did not diffuse out from the network at pH = 8 [71].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several articles describing the release of low molecular weight drugs from polysaccharide microcapsules. Thus, it was shown in [16][17][18][19] that multilayer microcapsules, whose shell has different thickness and composition, provide effective prolonged release of water-soluble drugs such as furosemide, ibuprofen and dexamethasone. In addition, the literature describes the yield of high molecular weight substances.…”
Section: Introductionmentioning
confidence: 99%